(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Mukha dushika or Youvana Pidaka mentioned under Kshudra Roga can be can be correlated to acne vulgaris in contemporary science. Mukha dushika defines as that which disfigures the face along with discoloration. As it is one of the major cosmetic problems which youth are facing, an attempt is made to cover all the treatment modalities mentioned in classics. References from various classical text books like Ashtanga Hrudayam, Ashtanga Sangraha, Susruta samhita, Basvarajeeyam, Chakradatta, Bhavaprakasha, Yogaratnakara, Gadanigraha etc are thoroughly reviewed and incorporated in this article. As Rasoushadhis are fast acting with very minimal dose, considering these various books like Rasatarangini, Rasamritam, Rasendra Sara Sangrahakara were also referred. Vamana, Siravyadha, Nasya, Abhyanjana are the Shodhana line of management. Lepas are the most common treatment modalities mentioned all classical text books. Rasaoushadhis also plays an important role in the management of Mukha dushika. Drugs like Manasila, Gorochana, Shilajatu, Sudha Parpati, Shankha Bhasma were noticed in the management of Mukha dushika. Apart from classical references some list of patent medicines is also helpful.